2020
DOI: 10.5937/turizam24-25540
|View full text |Cite
|
Sign up to set email alerts
|

The effect of servicescape in hotels on customer satisfaction: Evidence from resort hotels

Abstract: The purpose of this study was to determine the impact of servicescapes in hotels on customer satisfaction. The sample of the study consists of foreign tourists staying in five-star resort hotels operating in Marmaris district of Muğla province between June 1-August 30, 2019. Data were collected from 225 hotel customers. Mean, standard deviation, confirmatory factor analysis, reliability analysis and regression analysis were used in analyzing the obtained data.The study revealed that servicescape in hotels has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…It is being mentioned earlier that well-designed servicescape is very important in service environment (Zemke et al, 2019). It is being supported by (Artuğer, 2020) that ambient conditions, decor, signs and symbols had a significant effect on customer satisfaction. The elements mentioned above are part of the physical servicescape.…”
Section: Relationship Between Servicescape and Guest Satisfactionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is being mentioned earlier that well-designed servicescape is very important in service environment (Zemke et al, 2019). It is being supported by (Artuğer, 2020) that ambient conditions, decor, signs and symbols had a significant effect on customer satisfaction. The elements mentioned above are part of the physical servicescape.…”
Section: Relationship Between Servicescape and Guest Satisfactionmentioning
confidence: 85%
“…The figure also stated the elements of other intangibles such as business cards, stationery, and uniform. In this modern era, servicescape can also be defined as the comprehensive physical environment perceived by customers and consists of elements such as facilities, furniture, signs, temperature, noise, cleanliness (Artuğer, 2020).…”
Section: Physical Servicescapementioning
confidence: 99%
See 1 more Smart Citation
“…This variable refers to the collective attitudes, beliefs and ethical principles shared by the occupants and stakeholders of a building or organization. Morale relates to the overall mood, satisfaction and motivation of individuals within the building, while values encompass the guiding principles, ideals and ethical considerations that shape their behaviours and decision-making (Artuğer, 2020). Prioritizing stakeholder morale and values in green buildings helps to build trust and enhance the organization's reputation (Li et al , 2018b).…”
Section: The Analysis and Discussion Of Findingsmentioning
confidence: 99%
“…intentions to stay in the hotel (Kirillova and Chan, 2018). For example, a study by Artuğer (2020) showed that factors that should be considered for fulfilling the needs of hotel guests were physical appearance of the hotel, room decoration, furnishing, elements such as the colours used in the hotel, the quality of furniture, odours, music, heating and cooling. These factors, including the interior designs, are considered as tangible values that should be allocated in the hotel aesthetics.…”
mentioning
confidence: 99%